IRON DEFICIENCY ANAEMIA AS RISK FACTOR FOR SIMPLE FEBRILE SEIZURES: A CASE CONTROL STUDY - Aziz, Khwaja Tahir; Ahmed, Naheem; Nagi, Abdul Ghaffar (Journal of Ayub Medical College Abbottabad, 2017)
Background: Febrile fits is common problem in children. Among other risk factors, iron deficiency anemia is considered as aggravating factor for febrile fits. Iron deficiency anemia is preventable and treatable disease. Aims & Objectives: To find out iron deficiency anemia as risk factor for febrile fits. Materials & Methods: It was retrospective, case control study. 30 cases of febrile fits were recorded. Control group of 30 cases was taken at the same time with same variables but without febrile fits. Their temperatures and weights were recorded and laboratory hematological parameters Hemoglobin, Hematocrit, Mean Corpuscular Volume (MCV), Mean Corpuscular Hemoglobin (MCH), Mean Corpuscular Hemoglobin Concentration (MCHC), Red Blood Count (RBC) and Red Cell Distribution Width values were collected and analyzed statistically with SPSS Ver 20.0 Results: Mean Hemoglobin, Hematocrit, RBC, MCV, MCH, MCHC and RDW had significant P value (P value <0.05) in case group as compared to control group. Conclusion: As Iron Deficiency Anemia is a risk factor for febrile fits, treatment and prevention of iron deficiency anemia can decrease incidence of febrile fits.IRON DEFICIENCY ANAEMIA AS RISK FACTOR FOR SIMPLE FEBRILE SEIZURES: A CASE CONTROL STUDY